Compguide: Acquisition and editing of computer-interpretable guidelines - Gonçalves, Filipe Manuel (2017)
The formalization of Clinical Practice Guidelines (CPGs) as Computer-Interpretable Guidelines (CIGs) has the potential to positively influence the behaviour of health practitioners by being available at the point and time of care. Existing tools for acquiring and editing CIGs for automatic interpretation present limitations in their ease of use and the support they offer to a CIG encoder. Besides characterizing these limitations and identifying improvements to include in future tools, this work describes the CompGuide Editor, a Protégé tool for the management of CIGs that guides a user throughout the several steps of CIG encoding, without requiring the user to have programming knowledge, and through the use of interfaces that are simple and intuitive.